FRI0372 Rituximab for ANCA Associated Vasculitis Refractory To Conventional Treatment: A Retrospective Study on 25 Patients. (15th July 2016) - Ayan, G.; Ugurlu, S.; Hatemi, G.; Seyahi, E.; Melikoglu, M.; Fresko, I.; Ozdogan, H.; Yurdakul, S.; Hamuryudan, V.
Abstract : Background: The efficacy of rituximab (RTX) in ANCA associated vasculitis (AAV) has been shown in controlled trials. Observational data reflecting its real life use in AAV is limited. Objectives: Here we present our experience with RTX therapy in AAV patients refractory to conventional treatment. Methods: We retrospectively reviewed the records of 25 AAV patients (11 men, 14 women; mean age 42.8±14.2 SD years; mean disease duration 45.5 ± 47.5 SD months) treated with RTX between 2011 and 2015 due to inadequate response or relapse under conventional treatment modalities. Among these 25 patiens the main types of involvement at baseline were renal involvement in 14 patients, pulmonary involvement in 16, upper respiratory system in 10, ocular in 2, peripheral nervous system in 2, CNS in 1, skin in 1 patient and ear in 2 patients. We assessed treatment response with disease activity using BVAS scores, decrease in corticosteroid dose, improvement in renal functions and other organ manifestations. Results: RTX was given for a median of 2 courses (range 1–5, courses given at fixed intervals in 21 patients) during a mean follow-up of 17.4±13.9 SD months. The reasons for RTX treatment were active renal disease in 11 patients, pulmonary involvement in 9, upper respiratory system involvement in 4, and CNS involvement in 1 patient. In addition to RTX, corticosteroids were used in 13 patients, azathioprine + corticosteroids in 7 patients, methotrexate + corticosteriods in 2 patients, solo azathioprine in 2 patients and RTX was given solo in 1 patient. At final assessment 22 patients were under follow-up, 1 was lost to follow-up after 7 months and 2 had died, due to renal failure in one and respiratory failure in the other patient. 17/25 (68%) patients were in remission (BVAS score 0) at the final assessment. 3/25 patients (12%) had experienced relapses during follow-up. The mean BVAS score during the final assessment was 1.6 ± 4.1. Mean corticosteroid dose was reduced from 42±21.9 mg/day to 15.5±21.0 mg/day (p<0.001).The last evaluation of patients with renal involvement showed stable disease in 6 improvement in 6 and worsening in 2 patients. Mean creatinine level had slightly improved from 2.1 ± 1.2 mg/day to 1.9 ± 1.4 mg/day (p=0.36). Proteinuria had decreased from 1686±1466 mg/day to 1010±1100 mg/day (p=0.02). RTX treatment was terminated in 2 patients because of infusion reaction. Four patients were hospitalized while being on RTX. The first had pneumonia and responded to antibiotics. The second patient with diffuse lung involvement had died. The third died due to renal failure and the last patient developed end stage renal disease. Conclusions: Our retrospective study showed that RTX is an effective treatment modality that enables corticosteroids tapering and remission in majority of AAV patients refractory to conventional treatment modalities. It was generally well tolerated with few serious adverse events. Disclosure of Interest: None declared